2016
DOI: 10.1242/dev.138305
|View full text |Cite
|
Sign up to set email alerts
|

Rx3 and Shh direct anisotropic growth and specification in the zebrafish tuberal/anterior hypothalamus

Abstract: In the developing brain, growth and differentiation are intimately linked. Here, we show that in the zebrafish embryo, the homeodomain transcription factor Rx3 coordinates these processes to build the tuberal/anterior hypothalamus. Analysis of rx3 chk mutant/rx3 morphant fish and EdU pulse-chase studies reveal that rx3 is required to select tuberal/anterior hypothalamic progenitors and to orchestrate their anisotropic growth. In the absence of Rx3 function, progenitors accumulate in the third ventricular wall,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 65 publications
3
65
0
Order By: Relevance
“…A similar pathway was shown in chick, where Bmp2 and Bmp7 activate Tbx2, which represses Shh expression in the caudal hypothalamus (Manning et al, 2006). Shh expression may also be mediated by Rx3/Rax, as in both zebrafish rx3 and mouse Rax mutants, Shh expression is lost accompanied by a hypothalamic patterning defect (Muthu et al, 2016;Orquera et al, 2016). Interestingly, this phenotype is only observed when Rax is knocked out prior to embryonic day (E) 8.5 in mouse embryos, whereas a more specific defect in specification and differentiation of hypothalamic neurons is revealed when Rax is knocked out later (Lu et al, 2013;Orquera et al, 2016).…”
Section: Box 2 Modular Changes In Hypothalamic Anatomy: a Means To Ementioning
confidence: 54%
See 1 more Smart Citation
“…A similar pathway was shown in chick, where Bmp2 and Bmp7 activate Tbx2, which represses Shh expression in the caudal hypothalamus (Manning et al, 2006). Shh expression may also be mediated by Rx3/Rax, as in both zebrafish rx3 and mouse Rax mutants, Shh expression is lost accompanied by a hypothalamic patterning defect (Muthu et al, 2016;Orquera et al, 2016). Interestingly, this phenotype is only observed when Rax is knocked out prior to embryonic day (E) 8.5 in mouse embryos, whereas a more specific defect in specification and differentiation of hypothalamic neurons is revealed when Rax is knocked out later (Lu et al, 2013;Orquera et al, 2016).…”
Section: Box 2 Modular Changes In Hypothalamic Anatomy: a Means To Ementioning
confidence: 54%
“…These signals establish discrete A/P zones (Kapsimali et al, 2004) and eventually help to define the boundaries of hypothalamic subregions ( Fig. 1B) (Muthu et al, 2016). The hypothalamus also has intrinsic dorsal/ventral (D/V) identity consistent with the alar, basal, and floor plate territories of the developing neural tube, and specific gene markers define these regions (Domínguez et al, 2011).…”
Section: Early Patterning Of the Hypothalamusmentioning
confidence: 99%
“…We found that disc1 is expressed in the developing hypothalamus in proliferating progenitor cells that line the posterior part of the 3 rd ventricle and lateral recesses (45,51). Studies in mice have shown that in Disc1 mutants, progenitor cells in the cortex exit the cell cycle, and differentiate, prematurely (41).…”
Section: Discussionmentioning
confidence: 87%
“…First, having initially acted as a morphogen to pattern the early hypothala- neurones of the tract of the post-optic commissure. 1,8,18,[27][28][29]36,44,45 However, future lineage-tracing studies that build on previous/recent studies 8,27,29,51 are needed to tease out which neurones require Shh non-autonomously vs autonomously; namely, to distinguish between neurones born from progenitors that respond to Shh (but do not express it) vs neurones that differentiate from Shh +ive progenitor populations.…”
Section: Anterior Progenitor Selection and Differentiationmentioning
confidence: 99%